Related donor transplants: has posttransplantation cyclophosphamide nullified the detrimental effect of HLA mismatch? - Tara M. Robinson; Ephraim J. Fuchs; Mei-Jie Zhang; Andrew St. Martin; Myriam Labopin; Daniel A. Keesler; Didier Blaise; Asad Bashey; Jean-Henri Bourhis; Fabio Ciceri; Stefan O. Ciurea; Steven M. Devine; et al. (Blood Advances, 2018)
Abstract: We sought to identify whether posttransplantation cyclophosphamide (PT-Cy) reduces or eliminates the detrimental impact of HLA mismatching on outcomes of HLA-haploidentical related donor transplantation for acute leukemia. Data from 2143 donor-recipient pairs (n = 218 haploidentical sibling; n = 218 offspring; n = 1707 HLA-matched sibling) with acute myeloid or lymphoblastic leukemia were studied. All received a calcineurin inhibitor for graft-versus-host disease (GVHD) prophylaxis while high-dose PT-Cy was also given to recipients of haploidentical transplant. Patient age correlated with donor-recipient relationship: haploidentical siblings donated to patients aged 18 to 54 years whereas offspring donated to patients aged 55 to 76 years. Therefore, transplant outcomes were examined separately in the 2 patient age groups. In patients aged 18 to 54 years, there were no significant differences in outcomes except chronic GVHD, which was lower after haploidentical sibling compared to HLA-matched sibling transplant (hazard ratio [HR], 0.63; P < .001). In patients aged 55 to 76 years, despite lower chronic GVHD (HR, 0.42; P < .001), graft failure (14% vs 6%; P = .003), nonrelapse mortality (HR, 1.48; P = .02), and overall mortality (HR, 1.32; P = .003) were higher after transplant from offspring compared with an HLA-matched sibling. These data demonstrate a superior outcome in older recipients when using an HLA-matched sibling instead of offspring, although there were differences in transplant platforms (GVHD prophylaxis and graft type) between the 2 groups. Validation of these findings requires a prospective randomized trial wherein the transplant platforms can be closely matched.